Advances in light water reactor technologies - Saito, Takehiko; SpringerLink (Online service). (New York Springer, 2011)
Advances in Light Water Reactor Technologies focuses on the design and analysis of advanced nuclear power reactors. This volume provides readers with thorough descriptions of the general characteristics of various advanced light water reactors currently being developed worldwide. Safety, design, development and maintenance of these reactors is book?s the main focus, with key technologies like full MOX core design, next-generation digital I&C systems and seismic design and evaluation described at length. Also covered are: -Technologies currently being developed and utilized in a number of countries worldwide -A number of new recent developments in light water reactors -Analyses of different types of light water reactors from leading academics working on design and analysis Advances in Light Water Reactor Technologies is the ideal book for researchers and engineers working in nuclear power that are interested in learning the fundamentals of advanced light water plants.
Application of Probabilistic Safety Analysis in Design and Maintenance of the ABWR -- The Advanced Accumulator: A New Passive ECCS Component of the APWR -- Severe Accident Mitigation Features of APR1400 -- Development and Design of the EPRTM Core Catcher -- Nuclear Power Development and Severe Accident Research in China -- Full MOX Core Design of the Ohma ABWR Nuclear Power Plant -- CFD Analysis Applications in BWR Reactor System Design -- Next Generation Technologies in the Digital I&C Systems for Nuclear Power Plants -- Advanced 3D-CAD and Its Application to State-of-the-Art Construction Technologies in ABWR Plant Projects -- Progress in Seismic Design and Evaluation of Nuclear Power Plants -- Index.
Electronic reproduction.
Keywords: Light water reactors; Electronic books